Recurrence of positive SARS-CoV-2 RNA in COVID-19: A case report. (April 2020) - Chen, Dabiao; Xu, Wenxiong; Lei, Ziying; Huang, Zhanlian; Liu, Jing; Gao, Zhiliang; Peng, Liang
Highlights: People with positive SARS-CoV-2 RNA from respiratory tract specimens are infectious sources of COVID-19. SARS-CoV-2 RNA from respiratory tract specimens may be persistent or recurrently positive during the course of this disease. Active surveillance of SARS-CoV-2 RNA should be performed for infectivity assessment. Abstract: The ongoing outbreak of COVID-19 that began in Wuhan, China, has constituted a Public Health Emergency of International Concern, with cases confirmed in multiple countries. Currently, patients are the primary source of infection. We report a confirmed case of COVID-19 whose oropharyngeal swab test of SARS-CoV-2 RNA turned positive in convalescence. This case highlights the importance of active surveillance of SARS-CoV-2 RNA for infectivity assessment.